x-6=7x

Simple and best practice solution for x-6=7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-6=7x equation:


Simplifying
x + -6 = 7x

Reorder the terms:
-6 + x = 7x

Solving
-6 + x = 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-6 + x + -7x = 7x + -7x

Combine like terms: x + -7x = -6x
-6 + -6x = 7x + -7x

Combine like terms: 7x + -7x = 0
-6 + -6x = 0

Add '6' to each side of the equation.
-6 + 6 + -6x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -6x = 0 + 6
-6x = 0 + 6

Combine like terms: 0 + 6 = 6
-6x = 6

Divide each side by '-6'.
x = -1

Simplifying
x = -1

See similar equations:

| x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 | | 3.2/16= | | (3x-4w)(5x-8w)= | | 8-4x=9-5x | | p=-3q+1 | | -3(4-3y)=3y+6 | | 2(6x+8)-5=12x+11 | | (2+3)x(3+3)=x | | 0.51m+0.03=0.4m-0.74 | | -7(k-1)-5=-2(k-6) | | 26=6(5+-1a) | | 7x+15=3(2-y) | | 5z+15=4z+5 | | y^2+4=400 | | [x/3-6]=(2x+4)(-1/2) | | 8y-3=-3 | | 20=3-(z+10) | | 3x+30=x | | -3(t-2)+9t=8t-6 | | -31-a=-(1-4a) |

Equations solver categories